1994
DOI: 10.1113/jphysiol.1994.sp020305
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory synaptic potentials in guinea‐pig substantia nigra dopamine neurones in vitro.

Abstract: 1. The properties of stimulus-evoked and spontaneous inhibitory synaptic potentials were examined in guinea-pig substantia nigra dopamine neurones in sagittal and coronal midbrain slices in the presence of glutamate receptor antagonists. 2. Focal electrical stimulation within the substantia nigra, cerebral peduncle, internal capsule or the striatum evoked a biphasic IPSP consisting of a fast and a slow component, with peak latencies of about 30 and 250 ms, respectively. The fast component was sensitive to chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 55 publications
7
60
1
Order By: Relevance
“…In contrast to the in vivo results, local stimulation of substantia nigra in vitro leads to both short latency and long latency (onset about 35 ms, time to peak around 150 ms; Hausser and Yung, 1994) IPSPs. The short latency IPSPs are blocked by bicuculline and picrotoxin whereas the long latency IPSPs are blocked by the selective GABA B receptor antagonists, CGP 35348 or 2-hydroxysaclofen, thereby identifying them as GABA A and GABA B IPSPs, respectively (Saitoh et al, 2004).…”
Section: In Vitro Recordingscontrasting
confidence: 83%
See 3 more Smart Citations
“…In contrast to the in vivo results, local stimulation of substantia nigra in vitro leads to both short latency and long latency (onset about 35 ms, time to peak around 150 ms; Hausser and Yung, 1994) IPSPs. The short latency IPSPs are blocked by bicuculline and picrotoxin whereas the long latency IPSPs are blocked by the selective GABA B receptor antagonists, CGP 35348 or 2-hydroxysaclofen, thereby identifying them as GABA A and GABA B IPSPs, respectively (Saitoh et al, 2004).…”
Section: In Vitro Recordingscontrasting
confidence: 83%
“…2. This unmasking effect is likely due to blockade of presynaptic GABA B receptors present on GABAergic afferents to substantia nigra (Giralt et al, 1990;Hausser and Yung, 1994;Shen and Johnson, 1997;Paladini et al, 1999a;Boyes and Bolam, 2003, see Misgeld, this volume), a property shared by the striatal, pallidal, and pars reticulata afferents (Paladini et al, 1999a but see Cameron and Williams, 1993). Thus, in vivo, most or all of the postsynaptic effects of striatal, pallidal, and pars reticulata GABAergic inputs in vivo appear to be mediated by GABA A receptors, with the GABA B receptors acting predominantly as presynaptic inhibitory autoreceptors.…”
Section: In Vivo Recordingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because loss of cholinergic PPN neurons were observed not only in PSP (75-80%) but also PD (43-57%) (Hirsch et al, 1987;Jellinger, 1988;Zweig et al, 1987Zweig et al, , 1989, the loss of cholinergic PPN neurons in both diseases could attribute to attentive and cognitive impairments and sleep deficiencies in these diseases (Scarnati & Florio, 1997). Both neuroanatomical (von Krosigk et al, 1992;Smith & Bolam, 1990) and electrophysiological (Häusser & Yung, 1994;Saitoh et al, 2004;Paladini et al, 1999) studies demonstrated that dopaminergic neurons, as well as cholinergic neurons, receive GABAergic inhibitory effects from the basal ganglia, particularly from the SNr. Consequently a BG-BS system appears to involve the interdigitation of motor information with information relating to reward and reinforcement by modulating the excitability of both dopaminergic and cholinergic systems.…”
Section: Disturbances Of Arousal State Attention and Cognitionmentioning
confidence: 99%